2022
DOI: 10.1002/cctc.202101910
|View full text |Cite
|
Sign up to set email alerts
|

Selective Alkyne Semi‐Hydrogenation by PdCu Nanoparticles Immobilized on Stereocomplexed Poly(lactic acid)

Abstract: Polymer-supported PdCu alloy nanoparticles with a palladium to copper atom ratio of 1 have been synthesized upon: (i) Coordination of palladium/copper acetate to 2,2'-bipyridineend functionalized poly(lactic acid) (PLA); (ii) Stereocomplexaation of PLA-based macrocomplexes of opposite stereochemistry, and (iii) metal reduction with hydrogen. The obtained supported PdCu nanoparticles were successfully applied in the semi-hydrogenation of industrially important alkynols, such as 3-hexyn-1-ol and 2-butyne-1,4-dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…It has had an exciting performance in the hydrogenation process. PdCu nanoparticles are synthesized through three steps, including I-synthesis of polylactide as a biodegradable and widely used polymer II-binding of polylactide to metal and formation of metal stereocomplexes based on polylactide III-reduction of metal using hydrogen (Figure 21) [70]. Hydrogenation by Cu nanoparticles catalyst [70].…”
Section: Copper Catalyst Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has had an exciting performance in the hydrogenation process. PdCu nanoparticles are synthesized through three steps, including I-synthesis of polylactide as a biodegradable and widely used polymer II-binding of polylactide to metal and formation of metal stereocomplexes based on polylactide III-reduction of metal using hydrogen (Figure 21) [70]. Hydrogenation by Cu nanoparticles catalyst [70].…”
Section: Copper Catalyst Applicationsmentioning
confidence: 99%
“…Figure 21.Syntheses of the nanoparticles catalysts PdCu, Pd, and Cu[70]. License number: 5680370589458.…”
mentioning
confidence: 99%
“…Recycling tests reaffirmed the catalyst's robustness and stability, even upon exposure to air. This offers a promising and efficient catalytic solution for industrial applications [21].…”
Section: Other Catalystsmentioning
confidence: 99%
“…As a low-cost metal with high electron density, copper (Cu) is often used as a secondary metal dopant to modify the physicochemical properties of the active metals. [19][20][21][22] The study by Jiang et al demonstrated that Cu reduced the d-band center of Pd in the PdCu 2 @MF-X catalyst, thus regulating the adsorption mode of CC and improving the selectivity to alkenes. 23 During the selective hydrogenation of alkynes, the dissociation of H 2 is usually the rate-determining step.…”
Section: Introductionmentioning
confidence: 99%